Spectrum of Clinical Care for the Surgical Geriatric Population - Safa Damiati; Abdulmalik Altaf; Adel Johari; Nisar H. Zaidi; Hala Alkhaldi (Journal of King Abdulaziz University: Medical Sciences, 2023)
Although there are numerous studies on the most common chronic diseases in Saudi Arabia, some data on the extent to which standards of clinical care for the geriatric population are lacking. Therefore, a comprehensive surgical geriatric clinical care assessment was done using Arabic language survey. Sixty patients over the age of 65 years, attending a surgical clinic, were surveyed between September 2010 and February 2011. Variables included age, marital status, education, and income. Morbidities included diabetes, hypertension, hyperlipidemia and osteoporosis. Patients were asked about the progress in their condition in one year. Assessment of prevention of complications was assessed by obtaining the proper related history. The mean of the study population age was 70. Diabetes mellitus accounted for 32% of the co-morbidities, hypertension 29%, hyperlipidemia 24%, and osteoporosis 15%. During a year, 50% of diabetics reported that their condition got worse, and 10% noted improvement. Hypertensive reported same condition or worse equally. Regarding prevention of complications, diabetic annual ophthalmologist visits occurred in 67%, dentist visits in 44%, and daily feet exam in 59%. Sixty-two percent of diabetics were not measuring their blood sugar daily. The current study detected a high number of geriatric problems and co-morbid conditions prompting health care providers to improve timely preventive, diagnostic and therapeutic interventions.